Factors thet inciden in the sustainable valorization of the rural urban landscape of the Arunta Intiorko transport Pachia-Tacna district 2016 - Salinas Morales, Lys Solange (2017)
Objetive: The present research is oriented to determine the factors that affect the sustainable valuation of the rural urban landscape in the transect Arunta Intiorko of the District of Pachía of Tacna. Method: The research focused its methodology under a qualitative approach, the research study is of pure or basic type, non-experimental design "ex post facto", is explanatory observational because it seeks an explanation of the facts, by establishing the relationship of dependence of the variables. Results: In relation to the results after the experience, the level of valuation is "low" in one (22.2%), the "average" level (72.9%) and the high level (4.9%). In general, the formulation of the factors affecting the sustainable valuation of the rural urban landscape is significant (mean 72.9%) (p <0.05). Conclusions: The research concludes that: In relation to the results obtained allowed to establish that the factors that affect the sustainable valuation of the rural urban landscape in the transect Arunta Intiorko, Pachía - Tacna District are: La conceptualización.